Nitrogen isotope evidence for manuring of early Neolithic Funnel Beaker Culture cereals from Stensborg, Sweden. (August 2017) - Gron, Kurt J.; Gröcke, Darren R.; Larsson, Mikael; Sørensen, Lasse; Larsson, Lars; Rowley-Conwy, Peter; Church, Mike J.
Abstract: Little is known about arable agriculture in the Early Neolithic (4000–3300 cal BC, Funnel Beaker Culture) of Southern Scandinavia. Archaeobotanical material is rare and few archaeological sites have yielded more than a small number of charred cereal grains. In this short communication, we present single-entity carbon and nitrogen isotope analyses of charred cereals from Stensborg, an early Funnel Beaker Culture site near Stockholm, Sweden. This cereal assemblage is important as it is large, well-preserved and consists of multiple crop species. Our isotopic results indicate that many of the Stensborg cereal crops had been manured and that there is intra- and inter-species variation in manuring. We interpret these data as evidence of an integrated regime of stock-keeping and small-scale agriculture in the early Funnel Beaker Culture near its northernmost limit. Highlights: Domestic cereals from the Swedish early Neolithic were analyzed. Carbon and Nitrogen isotope analyses indicate manuring was practiced. There is inter- and intra-species variation in manuring practice. An integrated regime of stock-keeping and small-scale agriculture is indicated.